2013
DOI: 10.1038/ja.2013.116
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, structural elucidation and biosynthesis of 3-hydroxy-6-dimethylallylindolin-2-one, a novel prenylated indole derivative from Actinoplanes missouriensis

Abstract: Many prenylated indole derivatives are widely distributed in nature. Recently, two Streptomyces prenyltransferases, IptA and its homolog SCO7467, were identified in the biosynthetic pathways for 6-dimethylallylindole (DMAI)-3-carbaldehyde and 5-DMAI-3-acetonitrile, respectively. Here, we isolated a novel prenylated indole derivative, 3-hydroxy-6-dimethylallylindolin (DMAIN)-2-one, based on systematic purification of metabolites from a rare actinomycete, Actinoplanes missouriensis NBRC 102363. The structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…9). 69 From a bioactivity-guided approach, an antifungal metabolite, 5-hydroxyl-5-methyl-2-hexenoic acid (221), was found from Actinoplanes sp. HBDN08 obtained from a soil sample collected in Harbin, China.…”
Section: Secondary Metabolites From Actinoplanesmentioning
confidence: 99%
“…9). 69 From a bioactivity-guided approach, an antifungal metabolite, 5-hydroxyl-5-methyl-2-hexenoic acid (221), was found from Actinoplanes sp. HBDN08 obtained from a soil sample collected in Harbin, China.…”
Section: Secondary Metabolites From Actinoplanesmentioning
confidence: 99%
“…It shows interesting morphological features and forms sporangia containing motile sporangiospores . We have shown that this strain produces several secondary metabolites, including alkyl‐ O ‐dihydrogeranyl‐methoxyhydroquinones and 3‐hydroxy‐6‐dimethylallylindolin‐2‐one . However, analysis of the secondary metabolite biosynthetic gene clusters of A. missouriensis by antiSMASH indicated that this strain had at least 10 secondary metabolite biosynthetic gene clusters .…”
Section: Introductionmentioning
confidence: 99%
“…SN-593 functions as a 6-DMATS and is involved in the biosynthesis of 6-dimethylallylindole-3-carbaldehyde. 18 Three IptA orthologues, IptA Am from Actinoplanes missouriensis, 19 6-DMATS Sa from Streptomyces ambofaciens (S. ambofaciens), and 6-DMATS Sv from S. violaceusniger have been recently identified and characterised. 20 SCO7467 from S. coelicolor A3(2) belongs to a gene cluster being responsible for the biosynthesis of 5-dimethylallylindole-3-acetonitrile and the encoded protein acts as a 5-DMATS (5-DMATS Sc ).…”
Section: Introductionmentioning
confidence: 99%